THE IMPACT OF PROMOTIONAL EXPENDITURE ON MSME PROFITABILITY: EVIDENCE FROM A CULINARY BUSINESS IN INDONESIA - Santi Pertiwi Hari Sandi; Asep Darojatul Romli; Laras Ratu Khalida; Dedi Mulyadi; Dwi Epty Hidayaty; Janatun Naima (Journal Of Resource Management, Economics And Business, 2026)
Purpose: This study aims to analyze the role of promotional expenditure in increasing business profits at Gudeg Eyang MSME, a traditional culinary business operating in Karawang, West Java. Research Methodology: The study employs a quantitative descriptive method with a case study approach. Data were collected from both primary sources (interviews with business owners) and secondary sources (financial reports and promotional records in 2025). The analysis includes identifying promotional costs, measuring changes in turnover and profit, and calculating Return on Marketing Investment (ROMI). Results: The findings indicate that promotional expenditure has a positive impact on business profitability. Annual promotional costs of IDR 6,410,000 contributed to an increase in monthly turnover from IDR 12,000,000 to IDR 16,000,000, resulting in a 177% increase in net profit. The ROMI reached 250%, indicating high effectiveness of promotional strategies. Limitations: This study is limited to a single MSME case and covers only one year of data (2025), which may restrict the generalizability of the findings to other sectors or regions. Contribution: This research contributes to the literature by providing empirical evidence on the effectiveness of promotional expenditure in improving MSME profitability, particularly in the context of digital marketing and local culinary businesses.